Additive manufacturing of energetic materials: Tailoring energetic performance via printing. (10th November 2022) - Chen, Nihan; He, Chunlin; Pang, Siping
Highlight: Summarize the additive manufacturing methods adopted by preparing energetic materials like nano-thermites and explosive organic compounds. Thorough presentation of different samples' performance. Points out the advantages and disadvantages of preparing energetic samples by different additive manufacturing methods, and propose the desirable future work. Abstract: Additive manufacturing (AM), also called three-dimensional (3D) printing, has been developed to obtain energetic materials within the past decade. 3D printing represents a family of flexible manufacturing techniques that enable fast and accurate fabrication of structures with complex 3D features and a broad range of sizes, from submicrometer to several meters. Various methods have already been explored, including templating, melting extrusion, inkjet printing and electrospray methods. It was demonstrated that the structure achieved by AM could be used to manipulate the reactivity of energetic or reactive materials by changing the flow of gases and entrained particles via architecture. By employing different AM techniques, energetic materials with controllable nanostructures and uniformly dispersed ingredients can be prepared. It is exciting to tailor the energy release without defaulting to change the formulation of the conventional method. The combustion and mechanical properties of conventional energetic materials can be retained at the same time. In this review, the preparation and characterization of AM energetic materials that have been developed in the last decade are summarized. Various AM techniques used in the fabrication of energetic materials are compared and discussed. In particular, formulations of energetic materials applied in AM, metallic fuels, binders and energetic fillers and their advantages in terms of combustion efficiency and other properties are proposed. Graphical abstract: Image, graphical abstract